2013
DOI: 10.1111/1467-8268.12045
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Family Planning in Sudan: Results from a Survey in White Nile, Kassala and Al‐Gadarif, 2008

Abstract: Barriers to family planning are examined in three states in Sudan; White Nile, Kassala and Al‐Gadarif. The study adopted a two‐stage cluster sampling design with calculated sample size of 520 households. Data on households' characteristics as well as the background characteristics of ever married women regarding reproductive health, their knowledge, attitude and practice of family planning, was collected. Both descriptive and analytical statistics were used to examine the factors influencing use of family plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Our result is similar to the finding from a study A study performed in Nigeria in 2013 concludes that the major cause for the non-use of modern family planning was intending to have more children, 33 (31.46%) followed by pressure from the husband and religious factors respectively 21 (12.5%), 18 (10.9%) [18]. Also, its consistent to finding from study conducted in the same region and revealed that religious as key factor for barriers to utilization of family planning services [19]. However, all contraceptive method not completely free and the women should pay to attain their preferable contraceptive methods.…”
Section: Discussionsupporting
confidence: 63%
“…Our result is similar to the finding from a study A study performed in Nigeria in 2013 concludes that the major cause for the non-use of modern family planning was intending to have more children, 33 (31.46%) followed by pressure from the husband and religious factors respectively 21 (12.5%), 18 (10.9%) [18]. Also, its consistent to finding from study conducted in the same region and revealed that religious as key factor for barriers to utilization of family planning services [19]. However, all contraceptive method not completely free and the women should pay to attain their preferable contraceptive methods.…”
Section: Discussionsupporting
confidence: 63%
“…The survey indicated that only 9 % of women used family planning methods, and the unmet need for contraceptive was 29 % (Federal Ministry of Health 2011). A review of literature (Ali and Okud 2013;Ahmed 2013;Brair and Eltayeb 2013) reveals that utilization of family planning in Sudan is influenced by many factors, with the level of education of women and their husbands and religious beliefs the most influential (Ali and Okud 2013). Women's low level of interest in family planning can be related to religious ideology; in Islamic countries, childbirth is always perceived as a natural practice.…”
Section: Study Limitationsmentioning
confidence: 99%